Entre cruzes e bandeiras : a Igreja Católica e os conflitos agrários no norte do Rio Grande do Sul (1960-2009) - Goes, Valdemar da Silva (2010)
Our study reflect introduction and paper Catholic Church, include PCE (Pastoral Commission of Earth) together in the Socials Movements of Earth in the North of Rio Grande do Sul State. It happened since 1960 until 2009. The Geography Scenario started in the old Sarandi Farm. It was divided in the first decade of Century XX. Our center preoccupation was to analyze big agrarian conflicts about the Earth in the North Region of Rio Grande do Sul State (Master, Natalino, Annoni and Coqueiros). It was to perceive the change and mediation of the Catholic Church together Socials Movement. In the first movement the paper of church was in the politic field activity and organization (syndical creation and combat in the communism). For second (Natalino Farm)the paper of church it was central because it was determinate and aggregate. For third (Annoni Farm), important alterations started in the paper of Catholic Church, cause Without Earth Workers Movement was structured (WEWM - MST). In this time politic-faction dimension exceed the limits about religion sphere. In the fourth and last (Coqueiros Farm)there is total absence about church mediation in the organizations of movement. In spite of there is hard tendency social movement s autonomy, later 1990. We concluded that ritual dynamics follow a logic and symbol produced for the Catholic Church. For last, our study looked to list a social fight s process, in a period of meddle century, in this scenario where propriety privation produced conflicts and many phases and faces about church inside Social Movement